Simple coupled ultrahigh performance liquid chromatography and ion chromatography technique for simultaneous determination of folic acid and inorganic anions in folic acid tablets. (15th January 2018) - Wang, Fenglian; Cao, Minyi; Wang, Nani; Muhammad, Nadeem; Wu, Shuchao; Zhu, Yan
Highlights: This method could simultaneously determine folic acid and inorganic anions. The RP-C18 column was utilized as the separation and matrix elimination column. The on-line matrix elimination for determining inorganics saved time and solvent. Abstract: Folic acid plays a significant role during periods of rapid cells division and growth. Pregnant women require folic acid daily, either from dietary supplements or folic acid tablets in order to prevent fetal neural tube defects. In this work, a simple coupled ultrahigh performance liquid chromatography and ion chromatography technique was developed for simultaneous determination of folic acid and inorganic anions in folic acid tablets. A reversed-phase C18 column was used as the pretreatment column for on-line separating inorganic anions from organics. Inorganic anions were concentrated in the concentration column. Under the optimal chromatographic conditions, good sensitivity and linear calibration-curves (r ≥ 0.9992) were obtained. Low detection limits were obtained in the range of 0.0032–0.40 mg L −1 for all analytes. Repeatability results were satisfactory with relative standard deviations less than 1.50% (n = 5). The developed method was utilized to analyze spiked folic acid tablet samples with good measured recoveries (92.4–107.4%).